Marathon training: Gender and age aspects - Reed, J.; Gibbs, J. C. (Marathon running: Physiology, psychology, nutrition and training aspects, 2016)
No presentation of marathon running would be complete without a discussion of gender and age aspects. Marathon running is one of the world`s oldest sports dating back to the ancient Greeks. However, it is only in the last 40 years that women and older runners have begun training for and competing in these 42 km (marathon distance) foot races. In the pages that follow, we will provide a brief history of several notable women and older runners that have shaped the history of marathon running. We will review the physiological differences such as body composition and oxygen carrying capacity between men and women as it relates to marathon training and performance. We will discuss the performance differences such as finishing time and pace strategy between men and women as well as comment on gender-specific training and injury characteristics. Specific to female runners, we will report on menstrual disturbances that may result from high exercise energy expenditure and/or low dietary energy intake frequently observed among runners, and training and running considerations during pregnancy. As apparent and highly researched are the physiological considerations of marathon running, the equally important musculoskeletal and psychological factors such as bone loss and disordered eating will be discussed. We will briefly review the cardiovascular, pulmonary and neuromuscular changes that occur with aging, and the impact of these changes on marathon training and performance. Finally, we will discuss the risk of medical problems and running-related injuries in older marathon runners and the emerging trend of younger marathon runners (<18 years of age).